Antitumor properties of arsenic trioxide-loaded CalliSpheres(®) microspheres by transarterial chemoembolization in VX2 liver tumor rabbits: suppression of tumor growth, angiogenesis, and metastasis and elongation of survival - Duan, Xuhua (Am J Transl Res, 2020)
This study aimed to investigate the antitumor effect of arsenic trioxide (ATO)-loaded CalliSpheres(®) microspheres (CSM) by transarterial chemoembolization (TACE) in rabbits with VX2 liver tumors. A total of 120 VX2 liver tumor rabbits were randomized into four groups (N = 30 for each group), which received ATO-loaded CSM by TACE (CSM-ATO group), ATO by conventional TACE (cTACE-ATO group), transcatheter arterial embolization using CSM (TAE-CSM group), and saline arterial injection (control group). Five rabbits in each group were sacrificed at 12 h, 3 d, 7 d and 14 d, and then tumor proliferation, apoptosis, and angiogenesis/epithelial-mesenchymal transition (EMT) markers were detected. Tumor volume, metastasis status and ascites were assessed at 14 d. Ten rabbits in each group were observed until death for accumulating survival calculation. Tumor volume and ascites were decreased in the CSM-ATO group compared to the cTACE-ATO and TAE-CSM groups. Pulmonary, abdominal wall and omentum metastases were reduced while accumulating survival was increased in the CSM-ATO group compared to the TAE-CSM group. However, no difference in metastasis foci or survival between the CSM-ATO and cTACE-ATO groups was discovered. Meanwhile, tumor apoptosis was promoted while proliferation was suppressed in the CSM-ATO group compared to the cTACE-ATO and TAE-CSM groups. Additionally, HIF-1α, VEGF and microvessel density were decreased in the CSM-ATO group compared to the cTACE-ATO and TAE-CSM groups. Additionally, twist, N-cadherin, vimentin and MMP-9 were reduced while E-cadherin was enhanced in the CSM-ATO group compared to the cTACE-ATO and TAE-CSM groups. In conclusion, ATO-loaded CSM by TACE suppressed tumor growth, angiogenesis, and metastasis and elongated survival in VX2 liver tumor rabbits.